Forging Innovative Leadership: The Power of Agility, Diversity, and Risk-Taking Configurations - Fernanda Bethlem Tigre (Merits)
Innovation is crucial for achieving and maintaining a competitive edge, especially evident in the digital business landscape, where the fourth and fifth industrial revolutions are occurring concurrently. Leadership behavior significantly influences the direction of organizations toward innovation. This study investigated whether a propensity for risk taking, along with a commitment to diversity and agility, promotes or impedes leaders’ innovative behavior. Fuzzy-set qualitative comparative analysis was employed to assess the data gathered from an online survey of 119 global leaders. The results exposed four distinct routes to fostering innovative behavior and three paths leading to noninnovative behavior that should be evaded. All conditions play a vital role in triggering innovative behavior. Conversely, the lack of these conditions can result in noninnovative leadership. This study’s novelty rests on the empirical evidence it provides about the paths guiding leaders toward innovative behavior and avoiding the danger of noninnovative leadership. These findings can assist managers and HR departments in pursuing certain paths for hiring and training managers to boost innovative behavior and preclude paths leading to noninnovative conduct.